EFEKTIVITAS VIRTUAL REALITY RELAXATION THERAPY TERHADAP PENURUNAN TINGKAT KECEMASAN PADA PASIEN DENGAN GANGGUAN KECEMASAN DI RSUD PROF. M. YAMIN PARIAMAN - HENDRO ZALMADANI; FEBRIA SYAFYUSARI; ALZA SYAPUTRA (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2026)
Adolescence is a developmental period characterized by biological, psychological, and social changes that may influence behavior and decision-making related to reproductive health. Lack of accurate information regarding sexual health may increase the risk of risky sexual behaviors among adolescents. One effort to prevent these problems is through reproductive health education using an approach that is appropriate to adolescents’ characteristics. This study aimed to determine the effect of Smart Sexual Education health education using a Peer Educator approach on adolescents’ knowledge and attitudes toward risky sexual behaviors at SMKN 2 Pariaman. This study employed a quantitative method with a quasi-experimental design using a one-group pretest-posttest design. The sample consisted of 35 students of SMKN 2 Pariaman selected through a purposive sampling technique. Data were collected using knowledge and attitude questionnaires administered before and after the health education intervention. Data analysis was conducted using univariate and bivariate analyses with statistical tests based on data distribution at a significance level of α = 0.05. The results showed an increase in adolescents’ knowledge after receiving Smart Sexual Education with a Peer Educator approach. The percentage of respondents with good knowledge increased from 22.9% to 80%, with statistical analysis showing a p-value of 0.001. Furthermore, positive attitudes among adolescents increased from 37.1% to 85.7%, with a p-value of 0.002. The study concludes that Smart Sexual Education health education using a Peer Educator approach has a significant effect on improving adolescents’ knowledge and changing their attitudes toward risky sexual behaviors. This approach can serve as an effective alternative strategy for reproductive health education in school settings. Keywords:Smart Sexual Education, Peer Educator, Knowledge, Attitudes, Adolescents, Risky Sexual Behavior